Slow Dos Attacks Detection And Mitigation - Sikora, Marek (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
This article investigates the detection and mitigation methods against Slow DoS (Demand of Service) attacks. This research is focused on Slowloris, Slow POST, Slow Read, and Apache Range Header attacks. Detection methods are based on network traffic analysis and anomalous traffic monitoring. When the attack is detected, the attacker is blocked and web server resources are released. Methods are implemented as an intrusion prevention system software.
Keywords: Slow DoS; network traffic analysis; network monitoring; Slowloris; Slow POST; Slow Read; Apache Range Header; detection; mitigation